Tindak Tutur Direktif dan Strategi Bertutur Guru Bahasa Indonesia dalam Pembelajaran Teks Artikel Populer Siswa Kelas VIII - Zaura, Tarisa; Tressyalina, Tressyalina; Noveria, Ena; Triana, Herlin (Paedagogie, 2026)
This study has two objectives. First, to describe the forms of directive speech acts used by Indonesian language teachers in the learning process in class VIII of SMP Negeri 1 Pancung Soal. Second, to identify the speech strategies used by Indonesian language teachers in the Indonesian language learning process in class VIII of SMP Negeri 1 Pancung Soal. This study is a qualitative study using a descriptive method. The results of this study also consist of two parts. First, there are five forms of directive speech acts used by teachers in Indonesian language learning in class VIII of SMP Negeri 1 Pancung Soal, namely: (1) directive speech acts of ordering, (2) directive speech acts of requesting, (3) directive speech acts of demanding, (4) directive speech acts of suggesting, and (5) directive speech acts of challenging. Second, there are four speech strategies used by teachers in Indonesian language learning for grade VIII at SMP Negeri 1 Pancung Soal, namely: (1) direct speech strategy without small talk, (2) direct speech strategy with positive politeness, (3) direct speech strategy with negative politeness, and (4) vague speech strategy. Based on the results of this study, it can be concluded that there are five forms of directive speech acts and four speech strategies used by teachers in Indonesian language learning in class VIII of SMP Negeri 1 Pancung Soal.